The Ring Analogy according to al-Ḥakīm al-Tirmidhī and Its Implications for Understanding walāya in Ibn ʿArabī's Fuṣūṣ al-ḥikam - Palmer, Aiyub (Journal of Sufi studies, 2018)
The ring analogy is generally associated with Ibn ʿArabī and his Fuṣūṣ al-ḥikam. However, al-Ḥakīm al-Tirmidhī uses this same analogy as a way of expressing various aspects of walāya within his original and multi-layered doctrine of the concept. The present article's understanding of Tirmidhī's ring analogy and its relationship to his doctrine of walāya builds upon the work of Radtke and others who have sought to explain the major features of Tirmidhī's doctrine. The use of the ring analogy by Tirmidhī and Ibn ʿArabī after him leads us to posit a shared mode of thought and expression that helps situate and elucidate Ibn ʿArabī's esoteric doctrine of walāya within a framework developed by Tirmidhī.